Mapping genes underlying ethnic differences in tuberculosis risk by linkage disequilibrium in the South African coloured population of the Western Cape - Rugamika, Emile Chimusa (Institute of Infectious Disease and Molecular Medicine, 2014)
Includes bibliographical references.